Philosophy education: “tut wuri handayani” as the spirit of process governance in Indonesia educational organization - Agus Hermawan; Emily B. Tan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
‘Tut Wuri Handayani’ is the slogan of the National Education of Indonesia, written in Sanskrit. It is a Philosophy of Education which was originally promoted by Ki Hajar Dewantara. Practically, it is an accumulation of educational processes that prioritize the transformation of good character and knowledge through Organization Governance that is instigated by educational leadership. In this regard, the paper utilizes literature review method to get information from researchers published in refereed journals regarding process governance, model of organization governance in school and synthesizes the information to show how “Tut Wuri Handayani” can be promoted by the school leaders in order that it can be integrated in the school governance. This paper invites researchers to apply qualitative research designs to explore the possibility of the implementation the Philosophy Education: “Tut Wuri Handayani” in Organization Governance of Schools in Indonesia.